Effects of BFR-RST on upper limb performance in boxers: a study based on physiological indices, anthropometric measurement indices, anaerobic power, and punching performance - Xu, QingLou; Fei, Jiaming; Mao, Ruiqiu; Liu, Lei; Fei, Cheng (Frontiers in Physiology, 2025)
IntroductionThis study examined the effects of a four-week, 40% arterial occlusion pressure blood flow restriction-specific repeated sprint training (RST) regimen on the upper-limb anaerobic capacity and punching performance of male collegiate boxers.MethodsThirty-six healthy participants were assigned to either a blood flow restriction training group (Experimental Group, EG, n = 18) or a conventional training group (Control Group, CG, n = 18). Physiological measurements indices and anthropometric measurement indices (resting heart rate, heart rate after Wingate test, upper arm tensed circumference, upper arm relaxed circumference, BPP), upper-limb anaerobic power indices (PP, MP, tPP, PD), and punching performance indices (peak punching speed, total number of 6s all-out punches, peak punching speed post 6s all-out punches) were recorded at T0 (pre-intervention), T1 (mid-intervention), and T2 (post-intervention).ResultsTwo-way repeated measures ANOVA revealed that, compared to the CG, the EG showed significant increases at T2 in upper arm tensed circumference (+4.6%), BPP (+11.24% at T1, +10.18% at T2), PP (+10.09% at T1, +9.03% at T2), MP (+12.29% at T1, +11.69% at T2), tPP (+16.00% at T1, +8.09% at T2), total number of 6s all-out punches (+8.4% at T2), and peak punching speed post 6s all-out punches (+10.7% at T2). In contrast, heart rate after the Wingate test (−3.2% at T2) and PD (−6.57% at T1, −5.59% at T2) decreased (p < 0.05), with significant group-by-time interactions observed at T2 (p < 0.05).DiscussionThis study demonstrates that both types of RST training effectively enhance upper-limb anaerobic power and strength in boxers, with the improvements from blood flow restriction training proving superior to those from conventional RST. Furthermore, while neither training method significantly affected peak punch speed, the BFR-RST program significantly outperformed conventional RST in terms of fatigue resistance, leading to notable enhancements in anaerobic power.